Usefulness of library orientation programs to newcomers:University of Sri Jayewardenepura - Nishanthi, Menaka; Wijayasundara, Nayana Darshani (Sri Lanka Library Association, 2019)
Attached
Keywords: Academic libraries, Newcomers, Novices, Freshers, Orientation programmes, University of Sri Jayewardenepura